Unconventional secretion of PARK7 requires lysosomal delivery via chaperone-mediated autophagy and specialized SNARE complex - Biplab Kumar Dash; Yasuomi Urano; Yuichiro Mita; Yuki Ashida; Ryoma Hirose; Noriko Noguchi (Proceedings of the National Academy of Sciences, 2025)
PARK7/DJ-1, a redox-sensitive protein implicated in neurodegeneration, cancer, and inflammation, exhibits increased secretion under stress. We previously demonstrated that, as a leaderless protein, PARK7 relies on an unconventional autophagy pathway for stress-induced secretion. The current study delves deeper into the mechanisms governing PARK7 secretion under oxidative stress triggered by the neurotoxin 6-hydroxydopamine (6-OHDA). Here, we revealed that 6-OHDA-induced autophagic flux is critical for PARK7 secretion. Downregulation of syntaxin 17 (STX17), a SNARE protein crucial for autophagosome-lysosome fusion and cargo degradation, hindered PARK7 secretion. Likewise, impairing lysosomal function with bafilomycin A1 (BafA1) or chloroquine (CQ) diminished PARK7 release, highlighting the importance of functional lysosomes, potentially in the form of secretory autolysosomes, in PARK7 release. We also found that 6-OHDA appeared to promote the unfolding of PARK7, allowing its selective recognition by the chaperone HSPA8 via KFERQ-like motifs, leading to PARK7 translocation to the lysosomal membrane through LAMP2 via chaperone-mediated autophagy (CMA). Additionally, a dedicated SNARE complex comprising Qabc-SNAREs (STX3/4, VTI1B, and STX8) and R-SNARE SEC22B mediates the fusion of PARK7-containing autolysosomes with the plasma membrane, facilitating the extracellular release of PARK7. Hence, this study uncovers a mechanism where 6-OHDA-induced autophagic flux drives the unconventional secretion of PARK7, involving CMA for PARK7 translocation to lysosomes and specialized SNARE complexes for membrane fusion events.